Forgotten Generation X. A Retrospective Look from the Future - Elena Leonidovna Omelchenko (Интеракция. Интервью. Интерпретация)
The conversation about generations reduces to people whose youth coincides with the contemporary times, with a growing interest to the problems and demands of those young people who demonstrate visible differences from the previous ones and cause anxiety or hope in adults. Generation X is from the past, the youth of Russian Xs is from the late 20th, early 21st century, if we focus on the accepted generational chronology. The relevance of talking about Generation X can be associated with the gaining popularity of the discussion about the 90s, about heroes and anti-heroes of the time of changes, hopes and disappointments. For the last 10-15 years, the main characters of the generational drama have been millennials and zoomers, while media attention is turning to the alpha generation, following the marketing experts. Generation X, people who belong to this group by birth, are lost between boomers and millennial and are almost forgotten. Turning to the research and projects of that time will allow us to focus on the characteristics of the “twenty-something” youth. A look back in time from a distance of 30-40 years will help to see what may have fallen out of sight and to find traces of the cultural activity of those youth in the present. The article will focus on the peculiarities of X gen youth times, on the symbolic and real battles on the cultural youth scenes, on the acceptance and resistance to the discursive construction of youth identity in the political, media and academic fields. The article will use references to the research projects conducted in those years, as well as to the publications on their results.